Socio-demographic Profile and Drug Sensitivity Pattern of Suspected Drug Resistant Tuberculosis among Patients in Regional Tuberculosis Reference Laboratory (R.T.R.L) of a Tertiary Hospital (Journal of Medicine, 2017)
Background: Drug resistant tuberculosis has been reported in all regions of the world. In this study we address the socio-demographic profile and drug sensitivity pattern as well as prevalence of drug resistance tuberculosis in a tertiary center (regional TB reference laboratory) in Bangladesh.Method: This Study was carried out in R.T.R.L. (Regional TB Reference Laboratory) in 250 bedded Chittagong General Hospital. Patients who were referred to R.T.R.L during the period July 2012 to July 2013 were included in the study. Total 100 patients with suspected drug resistant tuberculosis (TB) who had any one of 9 criteria of NTP (National Tuberculosis Control Programme) were selected consecutively. Gene xpert MTB/RIF (Rifampicin resistance) test for all sputum positive cases were performed. Sputum sample of Patients with positive microscopy for AFB or positive Xpert/MTB was sent for culture. The samples with positive sputum culture were sent for drug sensitivity test for 1st line anti- tubercular drug.Result: Among 100 patients 78 were male and 22 were female, majority of the patients (64) were between 15-45 years with poor socio economic condition (73%) and primarily educated. Analysis of our Study result showed that 18% of patients were mono-drug resistant. Among them 13% showed resistance to isoniazid (INH), 4% to streptomycin and only 2% to rifampicin. No patient was found resistant to pyrazinamide (PNZ) and 38% of patient with suspected drug resistant TB was found to have no drug resistance. 18% of patient had multidrug resistant tuberculosis (MDR-TB) among which 56% were relapse cases (48% after cat -I, 8% after cat II), 24% were non converter of cat I, 12% belonged to failure of cat I, 3% failure of cat II, 2% return after default and others. 1% of patient had history of contact with MDR TB patient.Conclusion: Drug-resistance tuberculosis especially MDR-TB, was higher in patients with previously incomplete anti-tuberculosis treatment. A high level of drug resistance among the re-treatment TB patients poses a threat of transmission of resistant strains to susceptible persons in the community. For this reason proper counseling of patients and attention towards the completion of the anti-TB treatment are needed.J MEDICINE July 2017; 18 (2) : 62-67